2009
DOI: 10.1021/jp903102u
|View full text |Cite
|
Sign up to set email alerts
|

pH-Dependent cis → trans Isomerization Rates for Azobenzene Dyes in Aqueous Solution

Abstract: Azobenzenes can function as molecular switches driven by their unusual cis <--> trans photoisomerization properties. The stability of an azobenzene-based switch depends on its rate of thermal relaxation, which is known to depend on the solvent environment, but few kinetic studies in aqueous media have been reported. We use nanosecond UV laser flash photolysis-transient absorption spectroscopy to measure thermal cis --> trans isomerization rates for mono- and disubstituted p-aminoazobenzenes and p-hydroxyazoben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
70
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 44 publications
(81 reference statements)
6
70
0
Order By: Relevance
“…However, the different reaction pathway identified in the present study involves the formation of other intermediates, most probably 4,4′‐dihydroxyazobenzene. It was reported that the cis isomer of 4,4′‐dihydroxyazobenzene showed a broad UV/Vis absorption band at approximately λ =460 nm in the range of λ =400 to 500 nm if the solution pH was increased from 7 to 12 . As the pH of the reaction mixture used in this study was 10, the additional absorption bands at λ =476 and 494 nm could be attributed to the cis isomer of the 4,4′‐dihydroxyazobenzene intermediate.…”
Section: Methodsmentioning
confidence: 55%
“…However, the different reaction pathway identified in the present study involves the formation of other intermediates, most probably 4,4′‐dihydroxyazobenzene. It was reported that the cis isomer of 4,4′‐dihydroxyazobenzene showed a broad UV/Vis absorption band at approximately λ =460 nm in the range of λ =400 to 500 nm if the solution pH was increased from 7 to 12 . As the pH of the reaction mixture used in this study was 10, the additional absorption bands at λ =476 and 494 nm could be attributed to the cis isomer of the 4,4′‐dihydroxyazobenzene intermediate.…”
Section: Methodsmentioning
confidence: 55%
“…[6, 19, 20] Moreover, azobenzene substitution can influence pH sensitivity of photoisomerization and solvent dependency of isomerization. [21] Our results strongly suggest, that substitution may also dramatically affect the tendency of the compounds to interact via π–π stacking or hydrogen-bond mechanisms, and thus may lead to strongly varying photochromic properties.…”
Section: Resultsmentioning
confidence: 84%
“…43,44 Thermal rates are enhanced at low pH where protonation at the azo moiety reduces the activation barrier. 16,[45][46][47] The dipolar character of the thermal transition state is proposed to be similar to that of the excited state. Thus in general, red-shifted azobenzenes are found to exhibit faster thermal relaxation processes.…”
Section: Modifying Photoswitching Wavelengths and Thermal Relaxation mentioning
confidence: 99%